Equity in digital healthcare - the case of Denmark - Jeppe Eriksen; Mette Ebbesen; Kristina Tornbjerg Eriksen; Camilla Hjermitslev; Casper Knudsen; Pernille Bertelsen; Christian Nøhr; Ditte Weber (Frontiers Media S.A., 2023)
As digital healthcare services are expanding in use and purpose in a Danish context so are the functionalities embedded in these, constituting citizens' access to healthcare services and personal health data. In Denmark, the impact of inequalities in digital healthcare remains largely unexplored, making it crucial to pay close attention to this aspect as the digital transformation of the sector progresses. According to the Danish Health Act (2019), the Danish healthcare system is required to ensure easy and equal access to healthcare, high-quality treatment, coherent patient pathways, freedom of choice, easy access to information, transparency, and short waiting times for every citizen. These are focal law-based requirements influenced by the digitalisation of healthcare. Hence, based on insights from a highly digitalised country, in this case, Denmark, this paper aims to initiate a discussion on inequities in digital healthcare, address current challenges, and consider future directions by elaborating on conceptual, ethical, evidence-informed, and methodological issues linked to inequities in digital healthcare. Specifically, this paper discusses why inequities in digital healthcare in a Danish context need increased attention, how health equity is embedded in Danish legislation and how it can be approached from an ethical perspective. The central focus revolves around the essential principles of empowerment, emancipation, and equity, which are being highlighted to emphasise that the digitalisation of healthcare should actively work towards preventing and avoiding the perpetuation of healthcare inequalities. The paper concludes by discussing future directions for ensuring a more sustainable, robust, and equitable digital healthcare system.